Co-operation and competition : the role of identity and social perferences - Chen, Hongyu (2013)
This paper presents an experiment of Tullock Rent-seeking Model with two layers of information available to participants, namely Intra-Group Information and Inter-Group Information. As social identity is believed to exert ambiguous effects on social welfare and efficiency, the experiment is designed to understand the roles of social identity in Tullock Rent-seeking Contest through providing various levels of information. Subjects are divided into groups according to preferences on paintings, and their identities are enhanced by coin-allocation games before they start the Tullock Contest. In the Tullock contest, the subjects are asked to compete for a prize, on the basis of teams, by contributing their endowments. In terms of subjects‟ choices of contribution, the sense of rivalry induced by holding different identities has a much stronger impact than the sense of belonging caused by sharing the same identity. Moreover, while considering the interactive effects between gender and information, we observe that male subjects generally behave more aggressively than female and the impact of identity on them could be enhanced by unveiling both Intra-Group and Inter-Group Information. Last but not least, the experimental results suggest that a heterogeneous team composition leads to higher degree of rent dissipation.